Identity Crisis in Strindberg’s Miss Julie and Chekhov’s The Cherry Orchard: A Psychoanalytical Study - Rana Al-Husseini; Lutfi Hmadi (European Scientific Journal, ESJ, 2024)
August Strindberg’s Miss Julie and Anton Chekhov’s The Cherry Orchard have always been recurrently analyzed within disputable studies concerning the characters’ psychoanalytic makeup, the characters’ breakdown at the break of a new social class, and a naturalistic, existential approach. Such a foundational approach for analysis is overpoweringly highlighted in the two plays within an unshakable regularity to the assumption that female identities in the two plays have undergone intense turmoil, toppled heavily in the middle of socioeconomic changes with the decline of aristocracy. However, this paper aims to juxtapose and compare the concept of identity crisis in association with the traumatic experiences of the two characters Miss Julie and Mrs. Ranyevskaia through a comparative psychoanalytic approach. It is inexplicable how the two addressed characters grapple with their different circumstances with fractured identities, where they fail to stand up for their social and gender roles and elevate their sense of individuation and selfhood in the middle of the surrounding deteriorations. Through a comparative analysis, this study lays the groundwork needed for exploring, interpreting, and investigating more nuanced reciprocal relationships associated with identity crisis.